1996
DOI: 10.1089/dna.1996.15.1063
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Ovalbumin Upstream Promoter-Transcription Factor, Hepatocyte Nuclear Factor 3, and CCAAT/Enhancer Binding Protein Control the Far-Upstream Enhancer of the Rat α-Fetoprotein Gene

Abstract: We have further characterized the most distal of the three alpha-fetoprotein (AFP) enhancers required for expression of the AFP gene in fetal hepatocytes and yolk sac endodermal cells. Almost total rat AFP enhancer 3 (E3) activity is driven by a 160-bp fragment at -6 kb containing three target regions for nuclear proteins that cooperate to stimulate transcription from the AFP and the thymidine kinase promoters in HepG2 hepatoma cells. Region 1, recently shown to be crucial for correct function of the enhancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Forty-five base pairs 3Ј of this HNF3 site is a C͞EBP binding site (26). Upstream of the HNF-3 site is a chicken ovalbumin upstream promoter-transcription factor (COUP-TF) binding site (27). Deletion studies have shown that all three of these sites contribute to MERIII activity in HepG2 cells (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-five base pairs 3Ј of this HNF3 site is a C͞EBP binding site (26). Upstream of the HNF-3 site is a chicken ovalbumin upstream promoter-transcription factor (COUP-TF) binding site (27). Deletion studies have shown that all three of these sites contribute to MERIII activity in HepG2 cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Upstream of the HNF-3 site is a chicken ovalbumin upstream promoter-transcription factor (COUP-TF) binding site (27). Deletion studies have shown that all three of these sites contribute to MERIII activity in HepG2 cells (27). Of these factors, COUP-TF and HNF-3 are particularly interesting because both of these, although generally associated with positive regulation, have been shown to be repressors in some situations (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the two transgenic analyses is likely to be due to the action of factors binding to sequences neighboring the GRE. Interestingly, the same set of transcription factors interacts with the two regulatory sequences that confer neonatal induction, the Tat GRUs and the sequences used in the transgenic study of Montoliu et al (16): the dimeric GRE they used is also a dimeric Ets-binding site (11) and the Afp enhancers contain numerous binding sites for C͞EBP and HNF-3 that could synergize with this dimeric GRE (32)(33)(34). Such an interpretation is supported by the observation that the Afp sequences contribute to the expression patterns of the construct in the liver, because a typical predominance in the pericentral region was seen (16).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the liver-enriched factors that have been identified, including hepatocyte nuclear factor 1 (HNF1), FoxA, HNF4, HNF6, and C/EBP, have been found to regulate members of this gene family (Gorski et al, 1986;Chevrette et al, 1987;Lichtsteiner et al, 1987;Cereghini et al, 1988;Feuerman et al, 1989;Zhang et al, 1991;Milos and Zaret, 1992;Bois-Joyeux and Danan, 1994;Thomassin et al, 1996;Song et al, 1998). These transcription factors are also expressed in tissues other than the liver, suggesting that the combined action of multiple factors is required for the liver-restricted expression of target genes, including members of the albumin family.…”
Section: Introductionmentioning
confidence: 99%